The PD-1 and CD28 molecules on T cells in peripheral blood are associated with the prognosis of patients with advanced breast cancer receiving paclitaxel chemotherapy - Ji Yang; Shuxian Qu; Xinhui Qi; Yongming Liu; Jianing Qiu; Ying Yu; Yino Wang; Zhendong Zheng; Huiying Yu (PLoS ONE, 2026)
Background T cells are the primary cell subset involved in antitumor immunity. Their functions depend largely on the repertoire of surface receptors. This study investigates the association between the expression of CD28 and PD-1 molecules on peripheral blood T cells and prognosis in advanced breast cancer (BC) patients undergoing paclitaxel chemotherapy, along with their roles in anti-tumor immunity. Methods Peripheral blood from 61 patients with advanced BC was analyzed by flow cytometry for immunophenotype before treatment. We investigated the effects of PD-1 and CD28 on anti-tumor responses of lymphocytes in two breast cancer cell lines in vitro. Results Patients with high CD28 and low PD-1 on T cells were more sensitive to chemotherapy. PD-1 blockade enhanced the cytotoxicity of peripheral blood mononuclear cells (PBMCs) against tumor cells with high expression of PD-L1, an effect dependent on CD28 expression on T cells. CD28 expression is associated with immune cell infiltration in BC tumor microenvironment, particularly CD8 + T effector memory (Tem) cells. The proportion of CD8 + Tem cells increased after treatment with anti-PD-1 antibodies in vitro. Clinical results show that most patients who do not respond to chemotherapy have high expression of CD3 + PD-1 + and low expression of CD8 + CD28 + . Combining the two markers distinguished patients with progressive disease more accurately. Additionally, patients with low CD3 + PD-1 + expression and high CD8 + CD28 + expression had longer progression-free survival (PFS). Conclusion The expression of CD28 and PD-1 on T cells can serve as potential biomarkers for assessing tumor progression, chemotherapy response and prognosis in advanced BC. BC patients with low PD-1 expression or PD-1 blockade exhibit increased induction of memory T cells during the anti-tumor immune response.